Blooming and Forage Characteristics of Twelve Native Forbs Subjected to Repeated Defoliation - Jessica L. Prigge; Eric Bisangwa; Jonathan D. Richwine; Keagan J. Swilling; Patrick D. Keyser (Agronomy, 2023)
Insect pollinators are in population decline due to environmental and chemical stressors. Including native forbs in pastures could benefit grazers and pollinators; however, their forage and flowering characteristics are not fully documented. The objectives of our research were to evaluate 12 native forbs for persistence, forage mass, nutrient composition, and flowering patterns under repeated defoliation. Twelve species were planted in a small-plot experiment in 2018. Response variables were measured from 2020 to 2022. Annual (partridge pea, PPEA, Chamaecrista fasciculata) and biennial (black-eyed Susan, BESU, Rudbeckia hirta) species established high (p < 0.05) plant populations during the first season; however, the PPEA declined (p < 0.05) in forage mass during 2021. Tall species (Maximilian sunflower, MSUN, Helianthus maximiliani; cup plant, CUPP, Silphium perfoliatum) increased in forage mass, produced high-quality forage, and flowered during early fall. Lanceleaf coreopsis (LCOR, Coreopsis lanceolata) produced consistent (p > 0.05) forage mass and flowered in spring. The purple coneflower (PURC, Echinacea purpurea), Illinois bundleflower (ILBF, Desmanthus illinoensis), and oxeye sunflower (OSUN, Helopsis helianthoides) produced high-quality, consistent (p > 0.05) forage mass and flowered mid-season. Interseeding the BESU, ILBF, PPEA, LCOR, PURC, OSUN, and MSUN or CUPP would produce high-quality forage and floral resources throughout summer.